ANALISIS PENGARUH BEBAN KERJA, KEDISIPLINAN TERHADAP KINERJA PEGAWAI DENGAN DIMEDIASI OLEH MOTIVASI: Studi pada Pegawai Di Balai Pendidikan Menengah Kabupaten Gunungkidul - Budiawan, Arjun; Widiastuti, Nur (Jurnal Riset Mahasiswa, 2024)
This study aims to analyze: (1) the effect of workload on employee performance, (2) the effect of discipline on employee performance, (3) the effect of workload on motivation, (4) the effect of discipline on motivation, (5) the effect of workload through motivation on employee performance, and (6) the effect of discipline through motivation on employee performance at Balai Pendidikan Menengah Kabupaten Gunungkidul where motivation is an intervening variable. This research is a quantitative research and a population research. The analytical method in this study uses the instrument item validity test and the reliability test. The analysis prerequisite test consists of the Multiple Linear Regression Test and the Coefficient of Determination Test. In testing the hypothesis using the T-Test, F-Test, and Path Analysis Methods. The results of this study indicate that: (1) there is a significant effect of workload on the performance, (2) there is a significant performance effect, (3) there is no significant effect of workload on motivation with significant 0.281 > 0.05, (4) there is a significant effect of discipline on motivation, (5) there is no significant effect of workload through motivation on employee performance, (6) there is no the significant effect of discipline through motivation on employee performance.